Joint space-frequency block codes and signal alignment for heterogeneous networks - Ali, Syed Saqlain (2018)
In this paper, we propose a new diversity-oriented space-frequency block codes (SFBC) and signal alignment (SA) enabled physical network coding (PNC) method for the uplink of heterogeneous networks. The proposed joint Dual-SFBC with SA-PNC design substantially reduces interference and enables connecting a larger number of users when compared with methods adopting interference alignment (IA) or PNC. The main motivation behind the dual SFBC and SA-PNC design is that it allows the efficient coexistence of macro and small cells without any inter-system channel information requirements. Numerical results also verify that the proposed method outperforms the existing SA-PNC static method without any additional information exchange requirement between the two systems while achieving the main benefits of IA and SA-PNC coordinated methods recently proposed.